2010
DOI: 10.2217/pgs.10.17
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E Reduces Cardiovascular Disease in Individuals with Diabetes Mellitus and the Haptoglobin 2-2 Genotype

Abstract: Aims Individuals with both diabetes mellitus (DM) and the Haptoglobin (Hp) 2-2 genotype are at increased risk of cardiovascular disease. As the antioxidant function of the Hp 2-2 protein is impaired, we sought to test the pharmacogenomic hypothesis that antioxidant vitamin E supplementation would provide cardiovascular protection to Hp 2-2 DM individuals. Materials & methods We determined the Hp genotype on DM participants from two trials (HOPE and ICARE) and assessed the effect of vitamin E by Hp genotype o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
98
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(101 citation statements)
references
References 37 publications
2
98
1
Order By: Relevance
“…Hp polymorphism has been documented as a major determinant for determining the risk of developing cardiovascular diseases in diabetes mellitus patients. However, the increased risk of cardiovascular disease was most prevalent in patients who possessed the Hp-2 gene, with the highest risk for individuals who carried the Hp2-2 allele [17]. Individuals with the Hp-2 gene experienced more risk for developing diabetic retinopathy, diabetic nephropathy, and atherosclerosis compared to those who carried the Hp-1 gene [18].…”
Section: Vitamin Ementioning
confidence: 99%
See 3 more Smart Citations
“…Hp polymorphism has been documented as a major determinant for determining the risk of developing cardiovascular diseases in diabetes mellitus patients. However, the increased risk of cardiovascular disease was most prevalent in patients who possessed the Hp-2 gene, with the highest risk for individuals who carried the Hp2-2 allele [17]. Individuals with the Hp-2 gene experienced more risk for developing diabetic retinopathy, diabetic nephropathy, and atherosclerosis compared to those who carried the Hp-1 gene [18].…”
Section: Vitamin Ementioning
confidence: 99%
“…Diabetes mellitus with cardiovascular diseases increases the burden of patient health through increased free radical oxygen species in the body. Although several clinical trials did not show that additional benefit of Vitamin E helps patients, it left researchers to investigate the possible polymorphism in the genetic profile of patients [17].…”
Section: Vitamin Ementioning
confidence: 99%
See 2 more Smart Citations
“…It was subsequently shown that the risk of CVD in T2D patients was five times higher if they had a dysfunctional allelic mutation in a gene encoding for haptoglobin [9]. Supplementation with vitamin E in these individuals was able to compensate the impaired antioxidant function of haptoglobin, thereby reducing their risk of stroke, myocardial infarction and cardiovascular mortality [10]. No such benefit was observed in patients with other haptoglobin genotypes.…”
Section: Editorialmentioning
confidence: 99%